Block Copolymer-Assisted Synthesis of Iron Oxide Nanoparticles for Effective Removal of Congo Red - Mohan K. Bhattarai; Moses D. Ashie; Sita Dugu; Kiran Subedi; Bishnu P. Bastakoti; Gerardo Morell; Ram S. Katiyar (Molecules, 2023)
Iron oxide nanoparticles (IONPs) were synthesized via a block copolymer-assisted hydrothermal method and the phase purity and the crystal structure were investigated by X-ray diffraction. The Rietveld analysis of X-ray diffractometer spectra shows the hexagonal phase symmetry of α-Fe2O3. Further, the vibrational study suggests Raman active modes: 2A1g + 5Eg associated with α-Fe2O3, which corroborates the Rietveld analysis and orbital analysis of 2PFe. The superparamagnetic behavior is confirmed by magnetic measurements performed by the physical properties measurement system. The systematic study of the Congo red (CR) interaction with IONPs using a UV-visible spectrophotometer and a liquid chromatography–tandem mass spectrometry system equipped with a triple quadrupole mass analyzer and an electrospray ionization interface shows effective adsorption. In visible light, the Fe2O3 nanoparticles get easily excited and generate electrons and holes. The photogenerated electrons reduce the Fe3+ ions to Fe2+ ions. The Fe2+/H2O2 oxidizes CR by the Fenton mechanism. The strong adsorption ability of prepared nanoparticles towards dyes attributes the potential candidates for wastewater treatment and other catalytic applications.